English for Specific Academic Purposes Mobile Learning Framework for Technical and Engineering Context: A Conceptual Framework - Azwin Arif, Abdul Rahim; Mohamed Amin, Embi; Rosseni, Din (IDOSI Publication, 2014)
Highly skilled workers promises a nation with high income and the quest for it, highly skilled workers especially in engineering and technical context would pronounce a greater needs for effective language and communication skills. In a macro view of language learning, the English for Specific Academic Purposes (ESAP) serve this notion entirely. The advancement of technology in the field of teaching and learning has given new paradigm to language learners and educators to move on from ‘in-class’ to ‘connected’ and from E-Learning to a more flexible and personalized - Mobile learning. This paper proposes a conceptual framework for English for Specific Academic Purposes mobile learning framework for technical and engineering context which enables language learners in engineering universities learn English through mobile devices. The framework proposed adaptation of eight Mobile Learning and E-Learningframeworks selected from the literature and EAP Need Analysis as suggested by Dudley-Evans and St John [1]. The study proposes modified Delphi technique to confirm the elements juxtaposed and a quantitative study via survey techniques and SEM PLS to verify the framework. The proposed ESAP mobile learning framework would benefits both learners of English in technical universities and language educators cum developers of mobile learning.